2021
DOI: 10.1016/j.annonc.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

VP4-2021: EMPOWER-Cervical 1/GOG-3016/ENGOT-cx9: Interim analysis of phase III trial of cemiplimab vs. investigator's choice (IC) chemotherapy (chemo) in recurrent/metastatic (R/M) cervical carcinoma

Abstract: Interim analysis of phase III trial of cemiplimab vs. investigator's choice (IC) chemotherapy (chemo) in recurrent/metastatic (R/M) cervical carcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 0 publications
1
34
0
2
Order By: Relevance
“…These data indicate the potential benefit of inhibiting PD-L1 but also the challenges in providing benefit to patients whose tumors do not express PD-L1. Promising results have also been reported recently with cemiplimab in second-line or later settings in patients with persistent, recurrent, or metastatic cervical cancer ( 39 ).…”
Section: Current Treatment For Persistent Recurrent or Metastatic Cer...mentioning
confidence: 81%
See 1 more Smart Citation
“…These data indicate the potential benefit of inhibiting PD-L1 but also the challenges in providing benefit to patients whose tumors do not express PD-L1. Promising results have also been reported recently with cemiplimab in second-line or later settings in patients with persistent, recurrent, or metastatic cervical cancer ( 39 ).…”
Section: Current Treatment For Persistent Recurrent or Metastatic Cer...mentioning
confidence: 81%
“…Recently reported data from the phase 3 EMPOWER trial of cemiplimab, an anti–PD-1 agent, in patients with recurrent, persistent, or metastatic cervical cancer who had disease progression with prior platinum-based chemotherapy have for the first time showed that anti–PD-(L)1 therapy can produce better outcomes than chemotherapy in this setting ( 39 ). This trial evaluated cemiplimab monotherapy vs investigator choice of single-agent chemotherapy; all patients had received one prior line of therapy, and 40.8% had received more than one prior therapy.…”
Section: Future Treatment Options In Cervical Cancer Targeting Hpv-me...mentioning
confidence: 99%
“…More importantly, overall survival was improved with a hazard ratio of 0.69 (95% CI 0.56–0.84; p < 0.001) in favor of cemiplimab. Median overall survival was 12.0 versus 8.5 months 21 . While PD-L1 targeted therapies are a welcome advance in treatment for these often-young patients, there is a high unmet need for novel therapies with more efficacy and broader applicability.…”
Section: Discussionmentioning
confidence: 95%
“…Recurrent or metastatic cervical cancer patients who had progressed after platinum-based CHT were treated with either cemiplimab or the investigators’ choice of CHT. An interim analysis of 608 patients clearly favored cemiplimab treatment with regards to OS (12.0 vs. 8.5 months, p < 0.001), PFS and ORR [ 98 ]. In summary, the current evidence on ICI for cervical cancer is encouraging; however, ORR for ICI monotherapy in patients progressing after platinum-based chemotherapy is still low.…”
Section: Discussionmentioning
confidence: 99%